Development and Evaluation of Straw Push-Through Assembly for a No-Till Drill - Singh, Manpreet; Khurana, H M; Grewal, P S (Journal of Agricultural Engineering, 2006)
Rice-wheat crop rotation is one of the most extensively adopted cropping systems of Northern India. In Punjab state, combine-harvesters harvest most of the paddy crop. Management of paddy residues is a major field problem. The study was aimed to design and develop a suitable attachment for a no-till drill, for direct drilling of wheat under paddy residue conditions. A straw push-through assembly was theoretically designed and developed which could work satisfactorily in conjunction with the no-till drill in combine-harvested paddy fields. The new machine can do the direct drilling of wheat in combine-harvested field easily as the main operational problem of straw accumulation was reduced significantly.